Evaluating the Effectiveness of Sanctions in Indonesia's Illegal Logging Law: A Normative Juridical Approach to Strengthening Environmental Protection - Rahmawati, Diah Ayu; Haryadi, Wahyu Tris; Haryono, Haryono; Endarto, Budi; Sumaryanto, Djoko (Eastasouth Institute, 2025)
This study evaluates the effectiveness of sanctions within Indonesia's legal framework for addressing illegal logging, focusing on the implementation of Law No. 18 of 2013 on Prevention and Eradication of Forest Destruction. Using a normative juridical approach, the research examines the current legal sanctions, their enforcement, and their impact on forest conservation efforts. Findings indicate that while the legal provisions establish substantial penalties, the application of sanctions suffers from inconsistency, corruption, weak enforcement mechanisms, and inadequate institutional capacity. Comparative analysis with international best practices reveals potential improvements, such as the use of satellite monitoring, stronger corporate accountability, and community-based forest management. The study proposes a series of policy recommendations, including the enhancement of penalties, the integration of advanced monitoring technologies, and the promotion of restorative justice practices. By addressing these gaps, Indonesia can strengthen its efforts to combat illegal logging and ensure more effective environmental protection.